Pengaruh Beauty Influencer Credibility dan Content Characteristic of Influencer’s Post Terhadap Customer Engagement dan Purchase Intention: Studi dada Followers dari Beauty Influencer Tasya Farasya - Emita Br Pelawi; Farida Indriani (Diponegoro Journal of Management, 2025)
The beauty industry in Indonesia has experienced significant growth in recent years, in line with the rapid rise of social media platforms such as TikTok, Instagram, and YouTube as marketing tools. This phenomenon has led to the emergence of influencer based marketing strategies, encouraging many brands to seek suitable influencer for collaboration. This study aims to analyze influencer credibility and content characteristics of influencer posts, which are considered to influence customer engagement and its implication on purchase intention. The research was conducted among followers of the beauty influencer Tasya Farasya.Data were collected through an online survey using Google Form. The questionnaire was distributed to 157 respondents who follow Tasya Farasya's social media accounts and access her beauty product content. This study was analyzed using the Structural Equation Modeling (SEM) method and processed using SmartPLS version 4.The results show that source expertise, source attractiveness, content design quality, and content creativity have a significant effect on customer engagement. However, source trustworthiness does not significantly influence customer engagement, nor does customer engagement significantly mediate the relationship between source trustworthiness and purchase intention. Furthermore, customer engagement is proven to have a significant effect on purchase intention, and most mediating paths show significant indirect effects. These findings contribute to a deeper understanding of influencer based digital marketing in the beauty industry.